Environmental Realities: Evaluating Climate Change Coverage of Philippine Online News Media - Pacoma, Marc Agon (Faculty of Communications Science, Dr. Soetomo University, 2019)
Climate change is one of the most pressing issues at the present time, imposing great threats to human life and society. With issues surrounding climactic information, media seemed to play the most important role in addressing this problem. The inadequacy of researches on climactic coverage by media had motivated the researcher to embark on this exploration. This content analysis compared daily coverage of online news portals (Philippine Daily Inquirer, Manila Bulletin and Philippine Star) on climate change and climactic science-related issues from 2015-2016. The results indicated that there was a relative increase on climate change coverage by the media in a span of two years. Environmental frames, government sources, the Paris Agreement, the news section, and wired photos were the dominant themes that emerged during the coding process, which reflects and resonates similar findings of research inquiries on climate change coverage.